African families' perceptions of traumatic brain injury in the Capricorn District :an Afrocentric perspective - Phalane, Koketso Emelia (University of Limpopo, 2017)
This study investigated the perceptions of African families of TBI. Caregivers and TBI victims were given the opportunity to talk about their TBI perceptions. The study revealed that people’s knowledge of TBI is not good. This is proven by the way in which the participants understood and explained the conditions the victims found themselves in, after the accidents and how their family members are. Findings reveal that culture does play a vital role in the perceptions of African people. The study illustrates that the perceptions are culturally-rooted. The study interviewed five individuals (n=5) with TBI and a total of nine caregivers (n=9) were interviewed. A total of fourteen (n=14) participants were interviewed. The study reveals that the causes of TBI were attributed a number of things. According to the participants TBI is caused by witchcraft, the will of God and ancestors. The study also helped highlight the beliefs and the cultural system of Africans. It also explained the reality of an African. The Afrocentric theory helped shape the study as it helped in explaining the importance of an Africans’ view. The Afrocentric theory postulates that Africans have a different reality from that of Westerns and it has been proven by the findings. Although the participants were told about TBI by the doctors, they still had their own explanations and attributions to the problem.
Thesis (M. A. (Psychology)) --University of Limpopo, 2017
Keywords: African families; Traumatic brain injury; Afrocentric perspective; Head-Wounds and injuries; Brain-Wounds and injuries; Traumatic tentorial herniation; Brain -- Abnormalities